Local Wisdom of Pesantren as Core Value in Building an Islamic Education Organizational Culture in Indonesia - Fauzi, Ahmad; Pelu, Ibnu Elmi AS; Suhairom, Nornazira (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This research aims to investigate and interpret the pesantren's local wisdom, which contains a set of value systems. It is used as social capital in building the organizational culture of Islamic education. Therefore, this study employed a qualitative approach. The data collection techniques were interviews and observation to gain an in-depth understanding. This study found that there was some construction of pesantren local wisdom values: a) the local wisdom of the pesantren is a representation of universal values originating from the al-Qur'an and al-Hadith, the habitualization of these values is used as the basis for various management of pesantren education, b) internalization of the values of local wisdom is believed to be able to generate positive energy in the form of encouragement the formation of ethical behavior for each individual in the organization, such as honesty, commitment, discipline, independence, and responsibility, c) internalization of the local wisdom values of Islamic boarding schools is believed to be able to increase performance productivity. Thus, it can be used as the basis for Islamic education and corporate organization, towards an organization oriented towards religious and moral values and creating an influential organizational culture.